PENGARUH REGENERASI PETANI TERHADAP TINGKAT EKSISTENSI SUMBER DAYA MANUSIA PETANI MUDA - Sari, Septiana; Munajat, Munajat; Oktarina, Yetty (AGRIBIOS, 2025)
Human resources working in the agricultural sector in Ogan Komering Ulu Regency are dominated by older farmers while the younger generation has very low interest in working in the agricultural sector. To attract the interest of young farmers requires the role of the government through agricultural extension activities in educating the benefits of agricultural extension workers and joining government programs through farmer groups, so that government support is able to meet the needs independently to attract the interest of the younger generation to become farmers. The research method used is the survey method and the sampling method used is sampling by chance with purposive sampling method. The population in this study were young farmers working in the agricultural sector in Ogan Komering Ulu Regency with a sample of 120 respondents. The results showed that agricultural extension activities have a significant and positive influence on the existence of human resources. Regeneration of human resources has a significant and positive influence on the level of existence of human resources of young farmers.